2002
DOI: 10.1001/archotol.128.11.1313
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Inflammatory Medial Meatal Fibrotizing Otitis

Abstract: IMFO has its own specific pathophysiologic characteristics, and perhaps also etiopathologic characteristics, which are still unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
17
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 7 publications
2
17
0
4
Order By: Relevance
“…2 However, none of the patients in that earlier report developed lichen planus. If the ear canal process in our patients represented an infrequent location of lichen planus, the isomorphic response (Koebner phenomenon) 7 may explain the pathogenesis in this secondary location, following possible initiation via minor, epithelial ear canal trauma.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…2 However, none of the patients in that earlier report developed lichen planus. If the ear canal process in our patients represented an infrequent location of lichen planus, the isomorphic response (Koebner phenomenon) 7 may explain the pathogenesis in this secondary location, following possible initiation via minor, epithelial ear canal trauma.…”
Section: Discussionmentioning
confidence: 81%
“…The clinical picture of the ear canal process in the presented patients was identical to that in our earlier report of idiopathic, inflammatory, medial meatal, fibrotising otitis. 2 Instead, Martin et al found a hyperkeratotic picture in auditory canal skin. Thus, in most cases of idiopathic, inflammatory, medial meatal, fibrotising otitis, the primary and only site of expression of the epithelial disease is in the medial ear canals.…”
Section: Discussionmentioning
confidence: 99%
“…formation of the ear canal atresia has started to develop, the treatment is difficult; the atretic process proper is not preventable anymore (4,7). The chronically inflamed, and damaged skin is prone to (repeated) purulent infections causing granulation, which certainly accelerates the final atresia formation (3,4,7). However, a meticulous treatment of infections and granulations does not stop the process, and, seemingly, the infection is not a causative factor in the progression of the medial meatal inflammation and relentlessly developing atresia proper.…”
Section: Discussionmentioning
confidence: 99%
“…In neither of our IMFO cases was the use of topical antibiotics in the inflammatory stage beneficial. Potent local corticosteroid treatment instead of antiseptic or antibiotic ear drops lessens most effectively the symptoms and also controls the progression of atresia (4,7). Possibly, the process resulting in atresia formation can even be prevented if the epithelial destruction caused by inflammation can be reversed or averted with corticosteroid treatment started early enough (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation